TODDY PRODUCTION MODELS OF PB 121 AND KHINA 1 COCONUT HYBRIDS - Margaretha M.M. Rumokoi; Rusthampin H. Akuba (International Coconut Community Journal, 1998)
Tapping PB‑121 for coconut toddy can possibly reduce the loss ofproduction due to Phytophora infection and increasesfarmers income. Experiment was conducted in order to know the potential production of toddy of PB‑121 hybrid compared to KHINA‑1. The experiment was carried out at Pandu Experimental Garden of Research Institute for Coconut and Palmae Manado, North Sulawesi. Fourteen spathes of sixty palms or each hybrid was tappedfrom May 1991 to May 1992. Observations were made on toddy volume and its sucrose content measured daily in the morning (07:00‑09:00) and afternoon (14:00‑18:00). Multiple regression models were used to fit the production and sucrose content pattern of toddy. The result showed that coconut toddy production of PB‑121 was higher than KHINA‑1 from each spathe. Ae average toddy production of PB‑121 was 52.99 litre per spathe and KHINA‑1 was 46 65 litre per spathe. The sucrose contents of KHINA‑1 and PB‑121 were not significantly different. Model of the toddy production of KHINA‑l and PB‑121 differed but there was no difference between the model ofsucrose content of those two hybrid coconut varieties.